Studi eksperimental kinerja mesin TV-1 (engine research test) berbahan bakar campuran diesel-biodiesel - Musa, Muhammad Iskandar; Paloboran, Marthen; Rahim, Ismail; Mandra, Mohammad Ahsan S; Herman (Jurnal Teknik Mesin Indonesia, 2024)
This research is a laboratory experimental research that uses research testing machines. Using biodiesel fuel, a mixture of oil and diesel fuel. The composition of the biodiesel mixture used in this research was B35, B40, and B50 into diesel fuel in millilitres (ml). Tests were carried out by varying the load and compression ratio (CR), namely loads of 3 kg, 5 kg, 8 kg, and compression ratios of 14, 16, and 18. Data collection used observation techniques using tables to record the study results obtained. By using descriptive analysis techniques in the form of graphs and tables to make it easier to find out the study results. The results of the study from the engine performance research tests obtained were that performance increased with increasing loading at low compression ratios with the addition of biodiesel to diesel fuel, while at high compression ratios, the greatest power was obtained from B35 mixed fuel. However, the lowest fuel consumption in the mixture composition is the B35 mixture. Meanwhile, the lowest emission density opacity obtained was in the mixture of B35 and B40 biodiesel.